Water operators' partnerships and their supporting role in the improvement of urban water supply in Da Nang. Issue 1 (2nd January 2020) - Wright-Contreras, Lucía; Perkins, Julie; Pascual, Maria; Soppe, Gerard
ABSTRACT: This work analyzes the main outcomes and success factors of the water operators' partnership (WOP) between the Dutch water operators' organization, VEI (formerly Vitens Evides International), and the Vietnamese water utility, Da Nang Water Supply Joint Stock Company (Dawaco), which took place from 2007 to 2010. The partnership is considered within broader international and regional funding programmes, including parallel national and regional WOPs. The article presents WOPs as key processes in larger operations of water infrastructure development and considers WOPs as relevant strategies that contribute to the improvement of urban water services at a global scale.